2006
DOI: 10.1002/ajp.20280
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in postural control and locomotion in chimpanzees (Pan troglodytes)

Abstract: Posture and locomotion are two of the most primitive and basic motor manifestations of an organism's behavior. Although the restrictions they impose on other motor functions are evident, few studies have considered the possibility of asymmetries in these behaviors in human and nonhuman primates, and how they might impact other asymmetries at higher functional levels. The aim of the current study was to explore in a group of 10 chimpanzees at the Madrid Zoo-Aquarium the degree of asymmetry in four behaviors rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The main problem is accepting that the asymmetries are applicable at the population level. With respect to the study of laterality in simple motor actions, researchers have demonstrated population preferences only in captivity, finding a greater preference for right- (Colell et al 1995a;Hopkins and Bard 2000;Hopkins and Fernández-Carriba 2000;Hopkins et al 2005b) over left-handedness Morcillo et al 2006). To date, researchers have observed no population preference in the wild (Boesch 1991;Marchant and McGrew 1996;McGrew and Marchant 2001;Sugiyama et al 1993) or in intermediate settings (Fletcher and Weghorst 2005;Mosquera et al 2007) in these tasks.…”
Section: Introductionmentioning
confidence: 97%
“…The main problem is accepting that the asymmetries are applicable at the population level. With respect to the study of laterality in simple motor actions, researchers have demonstrated population preferences only in captivity, finding a greater preference for right- (Colell et al 1995a;Hopkins and Bard 2000;Hopkins and Fernández-Carriba 2000;Hopkins et al 2005b) over left-handedness Morcillo et al 2006). To date, researchers have observed no population preference in the wild (Boesch 1991;Marchant and McGrew 1996;McGrew and Marchant 2001;Sugiyama et al 1993) or in intermediate settings (Fletcher and Weghorst 2005;Mosquera et al 2007) in these tasks.…”
Section: Introductionmentioning
confidence: 97%
“…Foot preference during locomotion in nonhuman primates has been conducted exclusively in captive conditions, and all relevant research has concentrated on prosimians (Varecia variegata: Forsythe and Ward 1987), New World monkeys (Callthrix jacchus: Hook and Rogers 2002) and great apes (Gorilla gorilla : Heestand 1986; Pan paniscus: Hopkins and de Waal 1995;P. troglodytes: Heestand 1986;Morcillo et al 2006;Hopkins, 2008;Pongo pigmaeus: Heestand 1986;Cunningham et al 1989), whereas there is no evidence in Old World monkeys. To date, most studies on foot preference under locomotor modes in nonhuman primates have focused on quadrupedal walking.…”
Section: Introductionmentioning
confidence: 99%
“…The present study indicates that the amount of torsion asymmetry within individual chimpanzees and gorillas is statistically significant ( table 4 ), and that it occurs in magnitudes not significantly different from those in individual humans, which suggests that African ape locomotion may produce forelimb lateralization. Although ape quadrupedal locomotion is considered to be largely symmetrical [Hildebrand, 1967;Vilensky and Larson, 1989], chimpanzees exhibit a tendency to angulate their torsos during quadrupedal gaits, either to the left or right [Larson and Stern, 1987], and studies on both captive and wild chimpanzees have identified gait lateralization at the individual level (but not at the group level) Hopkins et al, 1997;Morcillo et al, 2006;Arcadi and Wallauer, 2011]. However, whether gorillas also exhibit similar lateralization is unknown, as are the effects that asymmetrical gait patterns might have on skeletal asymmetries [Carlson, 2006].…”
Section: Humeral Torsion Asymmetries In Humans and African Apesmentioning
confidence: 99%